PEMBELAJARAN OUTBOUND SAINS YANG BERMAKNA (MEANINGFUL LEARNING) DAN INOVATIF DI MADRASAH IBTIDAIYAH - Zulvia Trinova (Ta'dib, 2010)
Outbound Science provides active and enjoyable learning atmosphere that guarantees students not easily to get fed up and tired during the learning process. Such supporting atmosphere facilitates the students’ comprehension on the concept of science. Outbound science learning is carried out in order that the students can experience directly the concept they are learning about, develop their logical reasoning and teach them to acquire spiritual, emotional and intellectual optimally. After all, innovative learning is intended to activate students in order to improve educational quality by promoting student-centered learning in which instructional materials are made to be related to students’ daily life experience and meaningful as well.Kata kunci: outbound sains, meaningful learning (pembelajaran bermakna), inovatif.